1996
DOI: 10.1126/science.274.5289.959
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Switchable Periodicities and Diffraction from Mesoscopically Ordered Materials

Abstract: Two switchable, mesoscopically periodic materials were created by combining crystalline colloidal array (CCA) self-assembly with the temperature-induced volume phase transition of poly(N-isopropylacrylamide) (PNIPAM). Body-centered-cubic CCAs of hydrated, swollen PNIPAM particles Bragg-diffract infrared, visible, and ultraviolet light weakly, whereas arrays of compact shrunken particles diffract efficiently. A tunable diffracting array was also created by embedding a CCA of polystyrene spheres within a PNIPAM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
712
1
15

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 851 publications
(734 citation statements)
references
References 29 publications
6
712
1
15
Order By: Relevance
“…Effect of Temperature P(NIPAMco-MAA) Microgel Series: DLS measurements were used to judge the hydrodynamic radius in the temperature range of 20-70 o C of the polymer microgels at pH (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Hydrodynamic radius of the polymer microgel particles is dependent upon temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effect of Temperature P(NIPAMco-MAA) Microgel Series: DLS measurements were used to judge the hydrodynamic radius in the temperature range of 20-70 o C of the polymer microgels at pH (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). Hydrodynamic radius of the polymer microgel particles is dependent upon temperature.…”
Section: Resultsmentioning
confidence: 99%
“…A zeta plus zetameter (Brookhaven Instrument Corp., NJ) was used for the measurements of zeta potential. Polymer microgels surface charge density was determined from the electrophoretic mobility measurements at a temperature (20-55 o C) and pH (3)(4)(5)(6)(7)(8)(9)(10). The measurements were carried out as a function of pH (3)(4)(5)(6)(7)(8)(9)(10) at 25 o C. The measurements were performed in a background electrolyte concentration of 1×10 -3 mol dm -3 NaCl (In order to remove variability and to keep constant the length of electrical double layer, background electrolyte is used) solution.…”
Section: Methodsmentioning
confidence: 99%
“…5,6) On the other hand, since closed-packed-colloidal crystals are able to be used as templates for inverse opals with perfect three-dimensional photonic bandgaps, 7) the close-packed colloidal crystals have received more attention than the non-closed-packed colloidal crystal.…”
Section: Introductionmentioning
confidence: 99%
“…However, this type of colloidal crystal is unstable and can be destroyed even by a weak disturbance. Weissman et al have proposed a new soft material shown in figure 5(C), which is a colloidal crystal embedded in a poly(N-isopropylacrylamide) hydrogel [77]. The lattice spacing in this colloidal crystal is tuned by the temperature-induced phase transition in the hydrogel.…”
Section: Crystalline Diffractionmentioning
confidence: 99%